2004
DOI: 10.1002/path.1671
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric galectin‐1 induces IL‐10 production in T‐lymphocytes: an important tool in the regulation of the immune response

Abstract: Galectin-1, a beta-galactoside binding protein that can occur as both a monomer and a homodimer, binds to leucocyte membrane antigens such as CD7, CD43, and CD45, and has immune-regulatory functions in several animal models of autoimmune disease. However, its mechanism of action is only partially understood. In this study, a marked increase in IL-10 mRNA and protein levels was demonstrated in non-activated and activated CD4(+) and CD8(+) T-cells, following treatment with a high concentration (dimeric form), bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 36 publications
4
63
0
3
Order By: Relevance
“…Subsequent studies suggested that Gal-1 may modulate the immune system by inducing cell death in activated T cells (23). The results of the present study suggest that the in vivo effects of Gal-1 may result from altered expression of IL-10 and IFN-␥ in T cells as opposed to directly altering T cell viability, consistent with previous results (48). IL-10 exhibits potent immunosuppressive activity, inhibiting T cell activation and Th1 cytokine secretion and decreasing costimulatory receptors on APCs (67,68).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Subsequent studies suggested that Gal-1 may modulate the immune system by inducing cell death in activated T cells (23). The results of the present study suggest that the in vivo effects of Gal-1 may result from altered expression of IL-10 and IFN-␥ in T cells as opposed to directly altering T cell viability, consistent with previous results (48). IL-10 exhibits potent immunosuppressive activity, inhibiting T cell activation and Th1 cytokine secretion and decreasing costimulatory receptors on APCs (67,68).…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, iGal-1 retained the carbohydratebinding specificity of Gal-1. More importantly, iGal-1 retained previously documented biological endpoints of Gal-1 activity on leukocytes, including the induction of PS exposure in activated neutrophils, MOLT-4 cells and CEM cells in the absence of cell death (26,29,30), the induction of Ca 2ϩ flux in activated neutrophils (30), the induction of apoptosis in T cells, CEM cells and MOLT-4 cells in the presence of DTT (23,24,26,46,79) and the ability to alter T cell cytokine production (48). Taken together, these results demonstrate that iGal-1 retains the biological activities of the Gal-1.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In vitro studies revealed that gal-1 limits the immune response, for example promoting apoptosis of Th-1 cells, inducing IL-10, or down-regulating pro-inflammatory cytokines [3,4].…”
Section: Introductionmentioning
confidence: 99%